Professional techniques for video game writing. - Despain, Wendy, ....- (Mellesley, Massachusetts : Peters, 2008)
How to break in and stay in / Beth A. Dillon -- Interactive script formatting / Wendy Despain -- Writing pitch docs and exec docs / Erin Hoffman -- Game documentation guide / John Feil -- Manuals, in-game text, and credits / John Feil -- Narrative design / Jay Posey -- Game writing at a distance / Chris Klug -- Writing in a team / Sande Chen, Maurice Suckling, and Anne Toole -- Getting the work done / Wendy Despain -- Writing for all audiences / Beth A. Dillon -- Writers in the recording studio / Haris Orkin -- Writing tutorials, press start ... to start / Andrew S. Walsh -- Writing strategy guides / Alice Henderson -- Writing for new IP / Rhianna Pratchett -- Script doctoring / Richard Dansky -- Game writing and narrative in the future / Evan Skolnick.
Keywords: Computerspelen; Scripts